Determining the purposefulness of new services on the grounds of the results of quantitative analysis - Drejeris, Rolandas; Bivainis, Juozas; Tunčikienė, Živilė; Drejerienė, Eglė (Journal of Business Economics and Management, 2013)
The goal of the present article is to propose a methodology for substantiating the purposefulness of new service development reasoned by the results of a quantitative analysis of the current situation. The core of determining the purposefulness of new service development is assessing and comparing two trends of service business development: new service implementation and the main alternative of this process – the expansion of the scope of the current services. The paper demonstrates how the authors consolidate, annotate and critique available research on some logical aspects of new service development in order to find more objective quantitative decisions. The study provides the methodology (process model) of determining the purposefulness of new service development. A new attitude is evidenced by discovering quantitative assessment according to different sets of criteria. The paper also improves the comprehension of the complex process of new service implementation – proves the necessity of the first step, i.e. the determination of the purposefulness of a new service, which is often missed by authors. Appropriate solutions, according to the results of the suggested quantitative analysis, would increase the objectivity of assessment and the probability of successful new services.First published online: 11 Jul 2013